“A Logic of Its Own”: Repetition in Coleridge’s “Christabel” - Channick, Debra (Romanticism and Victorianism on the Net, 2008)
AbstractThis essay argues that Samuel Taylor Coleridge’s notoriously disjointed poem “Christabel” displays a consistent concern with repetition: thematically, formally, and psychologically. By looking at the pervasiveness of echoes, I show how “Christabel” produces a coherent exploration of repetition, first in terms of paralysis, and later in terms of creativity.